Transfer of know-how to small and mid-size businesses in Georgia, Moldova and Ukraine. White paper: Georgia - Maya Grigolia; Lasha Labadze; Pavol Minarik; Alena Zemplinerova; Marek Vokoun (Center for Social and Economic Research (CASE), 2015)
The report summarizes the conditions of the small and medium size enterprises (SME) sector in Georgia, identiies main problems in their development and provides recommendations for further interventions based on the Czech experience, research of existing literature and own survey among SME stakeholders in Georgia. Georgia is a small open economy. Its structure has been changing during last decade dramatically what provides opportunities for start-up companies. The revealed comparative advantage is in mineral waters, nuts and wine, but the opportunity to export also encompass metals, electricity, chemicals, stone, glass and clothing. One of the fast growing industries is tourism. Exports have increased over the period, although Georgia remains to be a net importer. Geogia attracts relatively large amount of foreign direct investment (FDI), large share of FDI in lowed from the European Union (EU) countries. Georgia receives favourable evaluations of its business environment. It ranks high in indices of economic freedom and it is among the top countries with respect to ease of starting and doing business. [...]
Keywords: D04; F23; L26; L30; M13; O25; O00; 330; small businesses; competition; liberalization; innovation; venture capital; business financing; skills and education